A Brief History in Cardiac Regeneration, and How the Extra Cellular Matrix May Turn the Tide - van der Pol, Atze; Bouten, Carlijn V. C. (Frontiers in Cardiovascular Medicine, 2021)
Tissue homeostasis is perturbed by stressful events, which can lead to organ dysfunction and failure. This is particularly true for the heart, where injury resulting from myocardial infarction or ischemic heart disease can result in a cascading event ultimately ending with the loss of functional myocardial tissue and heart failure. To help reverse this loss of healthy contractile tissue, researchers have spent decades in the hopes of characterizing a cell source capable of regenerating the injured heart. Unfortunately, these strategies have proven to be ineffective. With the goal of truly understanding cardiac regeneration, researchers have focused on the innate regenerative abilities of zebrafish and neonatal mammals. This has led to the realization that although cells play an important role in the repair of the diseased myocardium, inducing cardiac regeneration may instead lie in the composition of the extra cellular milieu, specifically the extra cellular matrix. In this review we will briefly summarize the current knowledge regarding cell sources used for cardiac regenerative approaches, since these have been extensively reviewed elsewhere. More importantly, by revisiting innate cardiac regeneration observed in zebrafish and neonatal mammals, we will stress the importance the extra cellular matrix has on reactivating this potential in the adult myocardium. Finally, we will address how we can harness the ability of the extra cellular matrix to guide cardiac repair thereby setting the stage of next generation regenerative strategies.